ACTIVE BYSTANDER BEHAVIORS AMONG HIGH SCHOOL STUDENTS: THE ROLE OF CO-OCCURRENCE OF VIOLENCE VICTIMIZATION AND PERPETRATION IN PERSONAL VIOLENCE PREVENTION - Ozaki, Reiko (2017)
Bystander programs aim to prevent personal violence, such as dating violence, sexual violence, sexual harassment, and stalking. They equip community members with skills to stop the violence before it happens by engaging in active bystander behaviors such as speaking up in potentially risky situations or supporting victims. Given that victimization and perpetration of personal violence, including co-occurrence, are common among youth, high schools have begun implementing bystander programs in recent years. This study examined the relationship between high school students’ experience of personal violence and their active bystander behaviors. Using the social identity approach as a theoretical foundation, this study hypothesized that polyvictims with two types of personal violence victimization would be more active as bystanders compared to those with no or one victimization experience. The study also hypothesized that polyperpetrators with two types of personal violence perpetration would be less active as bystanders compared to those with no or one perpetration experience. The study utilized a secondary dataset from a five-year study, Green Dot across the Bluegrass, which examined the effectiveness of the bystander program Green Dot in reducing rates of personal violence. Using network visualization techniques, commonly co-occurring violence types were identified. Cross-tabulation was used to examine the relationship between experience of co-occurring violence and individual characteristics, including sex, grade, sexual orientation, and exposure to parental partner violence. One-Way Analysis of Variance (ANOVA) was conducted to examine differences in active bystander behaviors based on victimization levels and on perpetration levels. One-Way Analysis of Covariance (ANCOVA) was also used to examine differences in active bystander behaviors based on victimization levels and perpetration levels after controlling for sex, rape myth acceptance, dating violence acceptance, and exposure to the bystander program. Findings revealed that polyvictimization and polyperpetration were both significantly associated with sex, grade, sexual attraction, and exposure to parental partner violence. Polyvictims showed significantly higher levels of active bystander behaviors than those with single or no victimization. Polyperpetrators also showed significantly higher levels of active bystander behaviors than students in other perpetration categories. Future research should include contextual variables such as level of injuries, intent of perpetration, and history of violence in order to more accurately distinguish victimization and perpetration. Suggestions for practice and policies include intervention in adult intimate partner violence to reduce impact on children. It is also recommended that bystander programs to be made relevant to students who are not exclusively heterosexual. Considering the potential presence of victims among participants, the program staff should be aware of impact of trauma and be prepared to provide support as needed. Finally, more rigorous investigation of the impact of bystander programs on youth who are victims as well as perpetrators is warranted